2017
DOI: 10.1101/110544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mTORC1 in AGRP neurons integrates exteroceptive and interoceptive food-related cues in the modulation of adaptive energy expenditure in mice

Abstract: Energy dissipation through interscapular brown adipose tissue (iBAT) thermogenesis is an important contributor to adaptive energy expenditure. However, it remains unresolved how acute and chronic changes in energy availability are detected by the brain to adjust iBAT activity and maintain energy homeostasis. Here, we provide evidence that AGRP inhibitory tone to iBAT represents an energy-sparing circuit that integrates environmental food cues and internal signals of energy availability. We establish a role for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Increased mTORC1 activity is associated with increased intracellular energy availability [20], [21]. We and others have shown that mTORC1 signaling participates in the regulation of energy balance by modulating the function of both POMC and AgRP neurons [22], [23], [24], [25], [26]. mTORC1 activity also regulates oxidative metabolism in POMC neurons, which, in turn, is critical for the appetite suppressant action of the hormone leptin [27].…”
Section: Introductionmentioning
confidence: 99%
“…Increased mTORC1 activity is associated with increased intracellular energy availability [20], [21]. We and others have shown that mTORC1 signaling participates in the regulation of energy balance by modulating the function of both POMC and AgRP neurons [22], [23], [24], [25], [26]. mTORC1 activity also regulates oxidative metabolism in POMC neurons, which, in turn, is critical for the appetite suppressant action of the hormone leptin [27].…”
Section: Introductionmentioning
confidence: 99%
“…Along this line, the AgRP response to food cues is accompanied by modulation of their physiological outputs. For instance, food sensory exposure in AgRP‐activated mice rapidly increases iBAT temperature to the level of control animals (Burke et al, 2017), revealing that acute sensory inhibition of AgRP neurons is sufficient to initiate whole‐body responses similar to that observed upon refeeding. Food perception also primes post‐prandial hepatic responses through the activation of ARH neurons expressing pro‐opiomelanocortin (POMC) (Brandt et al, 2018).…”
Section: Agrp Neuronal Regulation In the Anticipatory Phasementioning
confidence: 99%
“…Interestingly, this circuit appears to extend to include forebrain hypothalamic neurons as well. Gastrointestinal infusions of nutrients, but not non-nutrients, rapidly reduce the neurophysiological activity of a subpopulation of hypothalamic neurons expressing orexigenic agouti related peptide (AGRP) (Beutler et al, 2017), and work of Blouet and colleagues has, in turn, implicated AGRP neuronal activity as an important determinant of BAT thermogenesis (Burke et al, 2017). Activating AGRP neurons reduces sympathetic outflow to BAT and reduces thermogenesis, while inhibiting these neurons leads to increased sympathetic outflow and increased BAT thermogenesis.…”
Section: Non-canonical Roles For Gut Vagal Afferent Signalingmentioning
confidence: 99%